Design, Characterization, and In Vitro Assays on Muscle Cells of Endocannabinoid-like Molecule Loaded Lipid Nanoparticles for a Therapeutic Anti-Inflammatory Approach to Sarcopenia - Eleonora Maretti; Susanna Molinari; Renata Battini; Cecilia Rustichelli; Eleonora Truzzi; Valentina Iannuccelli; Eliana Leo (MDPI AG, 2022)
Inflammatory processes play a key role in the pathogenesis of sarcopenia owing to their effects on the balance between muscle protein breakdown and synthesis. Palmitoylethanolamide (PEA), an endocannabinoid-like molecule, has been well documented for its anti-inflammatory properties, suggesting its possible beneficial use to counteract sarcopenia. The promising therapeutic effects of PEA are, however, impaired by its poor bioavailability. In order to overcome this limitation, the present study focused on the encapsulation of PEA in solid lipid nanoparticles (PEA-SLNs) in a perspective of a systemic administration. PEA-SLNs were characterized for their physico-chemical properties as well as cytotoxicity and cell internalization capacity on C2C12 myoblast cells. Their size was approximately 250 nm and the encapsulation efficiency reached 90%. Differential scanning calorimetry analyses demonstrated the amorphous state of PEA in the inner SLN matrix, which improved PEA dissolution, as observed in the in vitro assays. Despite the high internalization capacity observed with the flow cytometer (values between 85 and 94% after 14 h of incubation), the Nile Red labeled PEA-SLNs showed practically no toxicity towards myoblasts. Confocal analysis showed the presence of SLNs in the cytoplasm and not in the nucleus. These results suggest the potentiality provided by PEA-SLNs to obtain an innovative and side-effect-free tool in the medical treatment of sarcopenia.